Richard Millet and “Literary Provocation” - Perko, Gregor (Populismo y propaganda: entre el presente y el pasado, 2020)
In 2012, Richard Millet, writer and editor, published a short text entitled Éloge littéraire d’Andrea Breivik [The literary praise of Andrea Breivik] which provoked a large media outcry. This “affair” leads us to ask ourselves a few questions. Firstly, we will be interested to know if the text was written out of pure provocation and if everything is allowed to the writer in the name of literature. Then, we will try to determine if the contemporary society is ready to engage in debate even on taboo subjects. Finally, we will answer the question of whether Millet’s essays can be considered populist.